Beyond the Archive: Bridging Data Creation and Reuse in Archaeology. Issue 2 (26th April 2018) - Faniel, Ixchel M.; Austin, Anne; Kansa, Eric; Kansa, Sarah Whitcher; France, Phoebe; Jacobs, Jennifer; Boytner, Ran; Yakel, Elizabeth
ABSTRACT: This article presents research on archaeological data creation and management practices at two excavations in Europe in order to gain a better understanding of how to align these practices with the data reuse needs of a broader research community. The Secret Life of Data project follows the life cycle of data from the field to the digital repository to better understand opportunities and challenges in data interpretation, publication, and preservation. Our "Slow Data" approach focuses not on maximizing the speed and quantity of data but, rather, on emphasizing curation, contextualization, communication, and broader understanding. Through a mixed-methods approach of interviews, field observations, and excavation data assessments, we recommended changes (both technical and organizational) to improve data creation and management practices. We report our findings and offer readers guidance on streamlining data collection for reuse during excavation. Abstract : Este artículo presenta los resultados de una investigación sobre la creación y gestión de datos arqueológicos en dos excavaciones en Europa con el objetivo de mejor entender cómo alinear esas prácticas con las necesidades de reutilización de datos de una comunidad de investigadores más amplia. El proyecto "La vida secreta de los datos" (cuya sigla en inglés es SLO-data) sigue el ciclo de vida de los datos desde su recolección en campo hasta su almacenamiento en un repositorio digital para entender oportunidades y retos relacionados con su interpretación, publicación y conservación. Nuestro enfoque basado en "datos lentos" ("Slow data") no busca maximizar la velocidad y cantidad de datos; al contrario, enfatiza su curación, contextualización, comunicación y mayor comprensión. Gracias a un planteamiento metodológico combinado que incluyó entrevistas, observaciones de campo y evaluación de datos de excavación, se elaboró una serie de recomendaciones (tanto técnicas como administrativas) para optimizar la creación y gestión práctica de datos. Presentamos los resultados del estudio y ofrecemos consejos para racionalizar la recolección de datos en campo con el fin de facilitar su reutilización futura.